APPLICATION OF INTERVAL TYPE-2 FUZZY LOGIC ALGORITHM FOR QOE EVALUATION IN WIRELESS COMMUNICATION NETWORKS - Ukpe, Kufre Christopher; Ojekudo, Nathaniel Akpofure (International Journal on Human-Computing Studies, 2021)
In this work, an application of interval type-2 fuzzy logic algorithm for evaluation of quality of service is proposed. The work uses delay, jitter, and packet loss as input parameters to evaluate the quality of service. The membership function (MF) terms, MF partitions, universe of discourse and linguistic variables is collected for use in designing the fuzzy logic model. The model was implemented using the Java programming language on Netbeans IDE. The implemented model was tested using 15 datapoints from the input module. The results of the system shows that when there is low rate (69) of network DELAY, low rate (10) of JITTER, and high rate (92) of PACKET LOSS then quality of service will not be so good (Moderate quality of service) (61% quality of service).